Mechanics and materials in the design of a buckling diaphragm wave energy converter. (15th August 2015) - Le, H.R.; Collins, K.M.; Greaves, D.M.; Bellamy, N.W.
Graphical abstract: Highlights: Design constraints of a diaphragm wave energy converter were identified. Transverse buckling of the diaphragm was related to the longitudinal sealibility. Material selection index was formulated to identify the best candidate materials. Minimum energy principle was applied to predict the shape of the diaphragm. Abstract: The design of a flexible wave energy device with a spine shape diaphragm proposed by Sea Energy Associates Ltd. was analysed. The operation of the device involves reversible buckling of a diaphragm in both longitudinal and transverse directions. The design constraints of the diaphragm were identified and Cambridge Engineering Selection software was applied to select candidate materials for the diaphragm structure. Best candidates of materials were identified for both laboratory scale and industrial scale. The initial curvature of the diaphragm was analysed using the minimum energy principle. The theoretical predictions of transverse deflection and longitudinal radius of curvature were in good agreement with measurements taken on a 1/10th scale-model of the diaphragm structure.